Thinking educational controversies through evil and prophetic indictment: Conversation versus conversion. Issue 1 (2nd January 2021) - Burke, Kevin J; van Kessel, Cathryn
Abstract: This article is about evil and its function in educational discourse. The research posits, using work in postsecularism and particularly through an historical, legal, and theological read of prophetic indictment and the function of the jeremiad in educational policy, that the terms of educational debate are rendered in a legal rather than a deliberative discursive framework. This lends itself, then, to the creation of evil others opposed to one's own preferred policy prescriptions and renders much of the discussion about and around the need for conversation and comity moot. The authors propose attending to the function of evil in education as well as positing an historical approach to thinking about why we often can't think differently about educational arguments.